The Influence Of Taxpayer's Knowledge And Awareness On Motor Vehicle Taxpayer Compliance (Sumedang Regency SAMSAT Empirical Study) - Masruri, Fahrul Alam; Herlina, Herni (LPPM Universitas Sebelas April, 2024)
The core problem of this research is the lack of taxpayer knowledge and taxpayer awareness in paying motor vehicle taxes in Sumedang Regency. This study aims to determine how much influence the knowledge of taxpayers and awareness of taxpayers has on taxpayer compliance in paying motor vehicle taxes in Sumedang Regency. This study uses quantitative methods or primary data. The method of determining the sample using probability sampling using the slovin formula. Data collection techniques using a questionnaire with a total of 100 samples. The data analysis technique used is Multiple Linear Regression Analysis. The results of this study indicate that the variable of taxpayer knowledge has a significant effect on taxpayer compliance in paying motor vehicle taxes and has an effect of 81.08%. The variable of taxpayer awareness has no significant effect on taxpayer compliance in paying motor vehicle taxes and has an effect of 80.55%. Simultaneously the variables of knowledge and awareness of taxpayers have a significant effect on taxpayer compliance in paying their motorized vehicle taxes and have an effect of 35.9%